In Eastern Region... CHES, Bhubaneswar, empowering horticultural growers - Singh, H S; Kishor, Kundan (Indian Horticulture, 2019)
The Central Horticultural Experiment Station (CHES), Bhubaneswar, was established as a regional station of IIHR, Bengaluru, with a vision of technological excellence for nationally competitive horticulture in the eastern region. The station has well-developed infrastructure like farm, office, irrigation facility including micro-irrigation, water harvesting structures, laboratory facility, library, nursery unit, ATIC centre, exhibition hall and training hall. The activities of the station are primarily centred on plant genetic resource management, development of varieties, production and protection technologies, outreach activities, transfer of technology and human resource development. During the period, the station has contributed to the horticultual development in the region.